PROBLEM SOLVING BAGIAN PENERIMAAN PASIEN DAN PENYIMPANAN BERKAS REKAM MEDIS (FILING) DI PUSKESMAS NGAGLIK II SLEMAN YOGYAKARTA - , JOKO DWIYANTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : The medical record as one of the gates leading in health care that as one measure of the quality of service provided to an institution to care give health service inspections. With the obligations and authority that has been given by the government to provide good service at the health center is necessary for equality of Quality Management Standards in the Institution. Therefore, to improve the process of accreditation needs to be done. Starting from patient admissions activity while registering to do storage. Of the activities of patient acceptance and storage problems are often found where the problem can interfere with quality of service. Thus, in this study researchers conducted problem solving in Patients Reception and storage by using Fish bone diagram in Ngaglik II Sleman Yogyakarta Health Center and is expected to resolve the problem. Objective : Identify the problem, problem solving and solutions related to Problem Solving in the Patient Reception and Medical Records Storage File (Filing) in Ngaglik II Sleman Yogyakarta Health Center. Methods : This study used a descriptive method with qualitative approach and study design using a phenomenological research design. Subjects of this study consisted of three officials at the medical record and the object of this research is the implementation of the medical records at the reception and storage of patient medical record file (Filing) in Ngaglik II Sleman Yogyakarta Health Center. Results : This study shows that the existing problems in the Health Center in Ngaglik II Sleman Yogyakarta, Preparation and implementation of Standard Operating Procedure (SOP)/Procedure constant (Protap) has enacted, there is accumulation of medical record file and the discrepancy between the draft Standard Operating Procedure (SOP) in the use of a queue card/system serial number, often errors in writing medical record numbers, medical record file returns are often delayed from the clinic to the MR, the systemis still manual, medical record number printed on the card that is owned by the patient sometimes does not exist, copying numbers medical record, medical record file misplacement into the rack, discrepancy sequence number and arrangement of the area, does not writing in the registers and making off without tracer medical record , MR've never done sorting active and inactive. It is influenced by factors 5M (Man, Method, Material, Money and Machine).